First report of human Trypanosoma cruzi infection attributed to TcBat genotype (2013)
Chagas disease is an endemic disease of the American continent caused by Trypanosoma cruzi and divided into six discrete typing units (TcI – TcVI ). Nearly 10 million people harbour the infection representing a serious issue in public health. Epidemiological surveillance allowed us to detect a bat?related T. cruzi genotype (henceforth named TcBat) in a 5?year?old female living in a forest area in northwestern Colombia. Molecular tools determined a mixed infection of T. cruzi I and TcBat genotypes. This represents the first report of TcBat infection in humans; the epidemiological consequences of this finding are discussed herein.